PEMANFAATAN LIMBAH IKAN NILA SEBAGAI FISHBONE HYDROXYAPATITE PADA PROSES ADSORPSI LOGAM BERAT KROM PADA LIMBAH CAIR - Gita Lokapuspita; Mirza Hayati; P Purwanto (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
The contaminant substance such as heavy metal is a serious environmental problem because its toxicity and nondegredable characteristic neither in biological or chemical way. Chrom (Cr) is one of the pollutant in a liquid waste that poisionous. Hydroxyapatite (Ca5(PO4)3(OH)) is a phospat crystal from calcium which has a hydroxyl ion and great capability as an ion exchanger and heavy metal adsorber. Fishbone hydroxyapatite is the natural hydroxyapatite from fishbone. This research investigates the fishbone hydroxyapatite adsorption capacity of the chrom (Cr3+) in  a laboratory study. The fishbone of nila burnt in a high temperature; 3000C and 6000C then grained and strained on 200 mesh measurement. The adsorption capacity of each fishbone hydroxyapatite, then be compared. The Langmuir’s adsorption isotherm equation Freundlinch’s adsorption isotherm equation can be used to get the characteristic and the maximum adsorption capacity of Cr3+. The difference of heat temperature influence the adsorption characteristic, adsorption power and adsorption capacity. At 300oC, the maximum adsorption Cr3+ capacity is 4,393 mg/gr and at 600oC, the maximum adsorption Cr3+ capacity is 5,540 mg/gr.